Ruling engines and diffraction gratings before Rowland: the work of Lewis Rutherfurd and William Rogers. - Brown, C. N. (Annals of Science, 2018)
Diffraction gratings are famously associated with Henry Rowland of Johns Hopkins University but there were precursors. Although gratings were first made and used in Europe, reliable machines for ruling gratings were developed in the USA, and two men, Lewis Rutherfurd and William Rogers, tackled the problem before Rowland. Rutherfurd, a wealthy independent astronomer, designed and built the first screw-operated engine for ruling diffraction gratings, the fore-runner of almost all subsequent ruling engines. With it he and his assistant D. C. Chapman ruled many gratings which he generously distributed to practising scientists, thereby materially advancing the science of spectroscopy. Rogers was a Harvard astronomer who developed an interest in the ruling of fine lines on glass that led him to construct a ruling engine with which he investigated the causes of the errors in the rulings he had examined. He continued to seek improvements with a second engine designed for ruling diffraction gratings. He ceased developing this engine when Rowland's excellent gratings began to be available, concentrating instead on related problems to which he could apply the knowledge and skills he had gained, but his investigations assisted Rowland and other later ruling engine builders. This paper brings together what is known about the ruling engines of Rutherfurd and Rogers, their development, the gratings they produced, their quality and the work that was done with them, and assesses and compares their achievements and the impacts of the work of these two men.